Exploring island syndromes: Variable matrix permeability in Phalaenopsis pulcherrima (Orchidaceae), a specialist lithophyte of tropical Asian inselbergs - Zhang, Zhe; Li, Jihong; Suddee, Somran; Bouamanivong, Somsanith; Averyanov, Leonid V.; Gale, Stephan W. (Frontiers in Plant Science, 2023)
Plants confined to island-like habitats are hypothesised to possess a suite of functional traits that promote on-spot persistence and recruitment, but this may come at the cost of broad-based colonising potential. Ecological functions that define this island syndrome are expected to generate a characteristic genetic signature. Here we examine genetic structuring in the orchid Phalaenopsis pulcherrima, a specialist lithophyte of tropical Asian inselbergs, both at the scale of individual outcrops and across much of its range in Indochina and on Hainan Island, to infer patterns of gene flow in the context of an exploration of island syndrome traits. We sampled 323 individuals occurring in 20 populations on 15 widely scattered inselbergs, and quantified genetic diversity, isolation-by-distance and genetic structuring using 14 microsatellite markers. To incorporate a temporal dimension, we inferred historical demography and estimated direction of gene flow using Bayesian approaches. We uncovered high genotypic diversity, high heterozygosity and low rates of inbreeding, as well as strong evidence for the occurrence of two genetic clusters, one comprising the populations of Hainan Island and the other those of mainland Indochina. Connectivity was greater within, rather than between the two clusters, with the former unequivocally supported as ancestral. Despite a strong capacity for on-spot persistence conferred by clonality, incomplete self-sterility and an ability to utilise multiple magnet species for pollination, our data reveal that P. pulcherrima also possesses traits that promote landscape-scale gene flow, including deceptive pollination and wind-borne seed dispersal, generating an ecological profile that neither fully conforms to, nor fully contradicts, a putative island syndrome. A terrestrial matrix is shown to be significantly more permeable than open water, with the direction of historic gene flow indicating that island populations can serve as refugia for postglacial colonisation of continental landmasses by effective dispersers.